The Application of CRISPR/Cas9 Technology in the Management of Genetic and Nongenetic Plant Traits - Wilbert Mutezo; Moosa M. Sedibe; Alina Mofokeng; Nemera Shargie; Tegwe Soko (International Journal of Agronomy)
Gene editing (GE) has yielded positive results in the management of genetic and nongenetic plant traits. Clustered interspaced palindromic repeats (CRISPR) and CRISPR-associated proteins (Cas) (together known as the CRISPR/Cas system) are relatively easy to use, compared to other existing genome editing technologies. The CRISPR/Cas tool produces unchanging gene mutations, with the ability to segregate from the Cas9/sgRNA construct to avoid similar modifications by CRISPR/Cas. CRISPR/Cas GE is fast and accurate; crops developed using this technique are resistant to viruses, fungi, and bacteria and resilient to abiotic and biotic stresses, while crops established using conventional methods take between 10 and 15 years to develop resistance. Therefore, CRISPR/Cas is a useful tool for sustainable agricultural production. Plant traits have been successfully manipulated using this technology. Notwithstanding the technical challenges of transferring CRISPR/Cas9 developed crops from the laboratory to the field, additional obstacles include uncertain policy systems, dispute over intellectual property ownership, and acceptability by consumers. Several Cas9-based applied techniques have gained popularity that enable researchers to enhance plants with speed and accuracy. In conclusion, the CRISPR/Cas9 system is a powerful technology for genetically modifying crops.